Source country characteristics and immigrants' migration duration and saving decisions - Murat G. Kirdar (Institute for the Study of Labor (IZA), 2010)
This paper examines how immigrants' migration duration and saving decisions in the host country respond to the purchasing power parity (ppp) and the wage ratio between the host and source countries. It is shown that in theory immigrants may stay longer in the host country as a result of an increase in ppp, in particular those with a high willingness to substitute consumption intertemporally. However, the empirical results from immigrants in Germany reveal that optimal migration duration decreases in ppp. Holding individual immigrant characteristics constant, immigrants from poorer source countries have shorter migration duration than immigrants from wealthier source countries. The empirical results also reveal that saving rate increases in ppp.
Keywords: F22; J61; 330; International migration; immigrant workers; Migranten; Dauer; Internationale Wanderung; Internationale Arbeitsmobilität; Kaufkraftparität; Sparen; Zeitpräferenz; Lohnstruktur; International; Deutschland